PENERAPAN METODE RATIONAL UNIFIED PROCESS PADA PERANCANGAN SISTEM PENGOLAH DATA ARISANKITA (Infotekmesin, 2019)
Arisankita is a business program owned by CV Dwi Idea Kreasi to assist the community in obtaining goods according to their needs and managed cooperatively. The management of the Arisankita system still relies on traditional accounting and is not yet computerized, especially during accessing and storing information. The purpose of this study is to discuss a web-based system for Arisankita's business program by applying the RUP method, to improve the accuracy of data processing at the company, to optimize automatic scheduling, and to increase efficiency, effectiveness and productivity. The RUP (Integrated Rational Process) Method is a system development process that covers the entire development cycle of a device that provides help to assist and be responsible for organizational development, which consists of 4 phases, including initial, elaboration, construction, and transition.